Farmers attitude towards the use of USG in rice cultivation in three selected villages of Netrakona district - Basak, NC; Pandit, JC (Journal of the Bangladesh Agricultural University, 2012)
The study was conducted to determine the attitude of farmers towards the use of urea super granule (USG) in rice cultivation and explore relationship between the selected characteristics of the farmers. Data were collected through personal interview from 84 randomly selected USG users in rice cultivation of the three villages under Sadar Upazila of Netrakona district during October to December 2008. A five point Likert scale was used to determine the attitude of farmers. The majority (73.81%) of the farmers had moderately favourable, 21.43% slightly favourable and 4.76% highly favourable attitude towards use of USG in rice cultivation. Level of education, farm size, annual income, farming information, agricultural training exposure and rice farming knowledge of the farmers had significant positive relationship but family subsistence pressure had significant negative relationship with their attitude towards the use of USG. DOI: http://dx.doi.org/10.3329/jbau.v9i2.10983 J. Bangladesh Agril. Univ. 9(2): 179185, 2011